Association between Clinical Case Validation and Students’ Success Rate in Virtual Pharmacy Simulation - Amirthalingam, Palanisamy; Hamdan, Ahmed Mohsen; Mohamed, Shahul Hameed Pakkir; Veeramani, Vinoth Prabhu; Thangam, Mathar Mohideen Nagoor; Alanazi, Majed Falah; Dhanasekaran, Muralikrishnan; Mani, Vasudevan; Alqifari, Saleh Fahad; Ali, Mostafa Abdelrahman Sayed (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Virtual simulation has been widely used in various pharmacy educational institutions worldwide, and it helps students approach the real-world pharmacy practice experience. However, the importance and practice of validating clinical cases among pharmacy educators still need to be improved. Objectives To assess the correlation between the success rate of students with reliability statistics, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). Materials and Methods One hundred and fifty students completed the twenty case scenarios comprising patient interviews, medication labeling, and counseling tasks. Students were randomly divided into an exam group (75 students) and a validation group (75 students). In the exam group, student passes percentages and the mean number of successes and failed students were calculated and compared using the students ‘ t-test. Reliability statistics, EFA, and CFA, were performed in the validation group to validate the clinical case scenarios. Spearman’s correlation was used to assess the correlation between the pass percentage of students and Reliability statistics, EFA, and CFA. Results The pass percentage of students had a significant positive correlation (p <0.05) with Cronbach’s α, McDonald’s ω percentage of variance, initial Eigen value, Comparative Fit Index (CFI), and Tucker-Lewis Index (TLI). Also, the Root Mean Square Error of Approximation (RMSEA) and Standardized Root Mean Square (SRMR) had a significant negative correlation (p <0.05) with the pass percentage of students. All these findings authenticate the relationship between the reliability, EFA, and CFA, and validated clinical cases significantly impact the pass percentage of students. Conclusion Pharmacy educators should ensure the validation of clinical cases, as validated clinical cases can enhance the learning experience. This may help to uplift the pharmacy practice experience and education.
Keywords: Correlation; Confirmatory factor analysis; Exploratory factor analysis; MyDispense; Pass percentage of students; Reliability statistics; Virtual simulation